(untitled) (Lex localis - Journal of Local Self-Government, 2024)
Urban water provision sits at the intersection of public administration, infrastructure policy, and social equity. In the Philippines, high aggregate access to drinking water coexists with uneven service reliability, coverage gaps, and persistent inefficiency—patterns that point to governance constraints rather than hydrological scarcity alone. This study examines how institutional structures and incentive systems shape urban water governance outcomes across five cities in the Zamboanga Peninsula (Region IX): Zamboanga City, Pagadian City, Dipolog City, Dapitan City, and Isabela City. The analysis applies a multi-level governance and institutional-incentive framework to trace how authority, resources, and accountability are distributed among national regulators and sector agencies (notably the National Water Resources Board and the Local Water Utilities Administration), local government units, and city water providers. The study adopts a comparative case design using publicly verifiable secondary data from 2022–2024, including utility performance reports and administrative records on service delivery and operational efficiency. Key indicators include service coverage, continuity of supply, and non-revenue water, alongside governance features such as tariff-setting influence, access to national financing, technical capacity, and the presence of cross-agency coordination mechanisms. Findings show persistent intra-regional disparities under a common national legal framework. Zamboanga City reports the highest coverage and continuity, but also the highest system losses, while smaller systems demonstrate lower coverage and more intermittent supply with only marginally better efficiency. Across cases, outcomes align less with formal decentralization than with fragmented mandates, weak regulatory enforcement, politically constrained tariff governance, and limited performance-linked funding—conditions that weaken accountability and dilute responsibility for results. The study proposes reforms focused on (1) tighter regulatory and planning coordination across levels, (2) performance-conditioned financing tied to measurable service and efficiency targets, and (3) transparent, insulated tariff review with structured stakeholder engagement to improve equity, reliability, and sustainability in regional urban water services.